Research on vulnerability analysis model of security accident system in petrochemical enterprises. Issue 1 (5th July 2021) - Dong, Mingxin; Meng, Yifei; Song, Xiaomiao; Qin, Chuanrui; Bai, Mingqi; Yin, Fabo; Zhao, Dongfeng
Abstract: Petrochemical enterprises store and process a large number of flammable, explosive, toxic and harmful chemicals, and their security protection systems are vulnerable. Once damaged by man‐made malicious will cause serious losses and adverse effects. Previous studies on the vulnerability of petrochemical enterprises have insufficient consideration of systematicity and uniqueness, and lack consideration of the correlation and game of vulnerability elements. In this study, from the perspective of system, the elements of the security accident system vulnerability are analyzed, and the vulnerability analysis model of security accident system is put forward by studying the interaction between the elements. Threat and exposure constitute the external vulnerability of security accident system, sensitivity and adaptability constitute the internal vulnerability of security accident system; and the threat plays a counter role with sensitivity and adaptability through exposure, which promotes the evolution of vulnerability; Moreover, the different vulnerability elements of security accident system evolve step by step, with the evolution of security accidents. Finally, an illustrative case proves the feasibility of the vulnerability analysis model proposed in this study. The results of this research enrich the theoretical research on vulnerability, provide a reference for the prevention and control of security accidents in petrochemical enterprises.